DiL-ZiHNiYET iLiŞKiSi BAGLAMINDA DiL-ÖGRENME VE DiL-SINIF iLiŞKiSi - Çavuşoğlu, Ali (Fırat University, 2005)
W e had set in anather paper that the mather language lıas an important and inıpressive role in the formatian of hurnan mentality. Tlıere is alsa a close relatiOJı between mather language and learning. Language changes by the way of cu ltıtre and the environnıent. Bul alsa takes clıarge a role to change the culture and people. White the language has been c/ıanging the mentality changes. It is possible to see in one 's language that lı o w he is looking to the world. And it is possible to form lı is mentality with the language. So we ıvill take in lıand the correlation between language-learning- nıentality; tlıen the correlation between language and social statute.
Keywords: Religious Studies; Din Araştırmaları